Elevated expression of the centromere protein‐A(CENP‐A)‐encoding gene as a prognostic and predictive biomarker in human cancers. Issue 4 (21st April 2016) - Sun, Xia; Clermont, Pier‐Luc; Jiao, Wenlin; Helgason, Cheryl D.; Gout, Peter W.; Wang, Yuzhuo; Qu, Sifeng
Abstract : Centromere protein‐A (CENP‐A), a histone‐H3 variant, plays an essential role in cell division by ensuring proper formation and function of centromeres and kinetochores. Elevated CENP‐A expression has been associated with cancer development. This study aimed to establish whether elevated CENP‐A expression can be used as a prognostic and predictive cancer biomarker. Molecular profiling of CENP‐A in human cancers was investigated using genomic, transcriptomic and patient information from databases, including COSMIC, Oncomine, Kaplan–Meier plotter and cBioPortal. A network of CENP‐A co‐expressed genes was derived from cBioPortal and analyzed using Ingenuity Pathway Analysis (IPA) and Oncomine protocols to explore the function of CENP‐A and its predictive potential. Transcriptional and post‐transcriptional regulation of CENP‐A expression was analyzed in silico . It was found that CENP‐A expression was elevated in 20 types of solid cancer compared with normal counterparts. Elevated CENP‐A expression highly correlated with cancer progression and poor patient outcome. Genomic analysis indicated that the elevated CENP‐A expression was not due to alterations in the sequence or copy number of the CENP‐A gene. Furthermore, CENP‐A can be regulated by key oncogenic proteins and tumor‐suppressive microRNAs. CENP‐A co‐expression network analysis indicated that CENP‐A function is associated with cell cycle progression. Oncomine analysis showed a strong correlation between elevated CENP‐A expression and oncolytic response of breast cancer patients to taxane‐based chemotherapy. In conclusion, elevated CENP‐A expression is coupled to malignant progression of numerous types of cancer. It may be useful as a biomarker of poor patient prognosis and as a predictive biomarker for taxane‐based chemotherapy. Abstract : What's new? Elevated expression of Centromere protein‐A (CENP‐A), a histone‐H3 variant with a regulatory role in cell division, has been associated with cancer progression. Using publicly available databases, this study demonstrates that elevated CENP‐A expression is coupled to malignant progression of numerous types of cancer. In particular, it can be used as a critically needed biomarker for ( i ) poor patient prognosis and ( ii ) predicting the response of breast cancer patients to taxane‐based chemotherapy.